Probing paracellular -versus transcellular tissue barrier permeability using a gut mucosal explant culture system. Issue 1 (2nd January 2019) - Danielsen, E. Michael; Hansen, Gert H.
ABSTRACT: Intestinal permeation enhancers (PEs), i.e. agents improving oral delivery of therapeutic drugs with poor bioavailability, may typically act by two principally different mechanisms: to increase either transcellular -or paracellular passage across the epithelium. With the aim to define these different modes of action in a small intestinal mucosal explant system, the transcellular-acting PE sodium dodecyl sulfate (SDS) was compared to the paracellular-acting PE ethylenediaminetetraacetic acid (EDTA), using several fluorescent polar – and lipophilic probes. Here, SDS rendered the enterocyte cell membranes leaky for the relatively small polar tracers Lucifer yellow and a 3 kD Texas red-conjugated dextran, but most conspicuously SDS blocked constitutive endocytosis from the brush border. In contrast, the main action of EDTA was to increase paracellular passage across the epithelium of both polar probes, including 10 – and 70 kDa dextrans and lipophilic probes, visualized by distinct stripy lateral staining of enterocytes and/or accumulation in the lamina propria. In addition, EDTA caused a loss of epithelial cell polarity by opening tight junctions for diffusion of domain-specific basolateral/apical cell membrane protein markers into the opposite domains. By transmission electron microscopy, SDS caused the formation of vacuoles and vesicle-like structures at the lateral cell membranes. In contrast, EDTA led to a bulging of the whole enterocyte apex, resulting in a "cobblestone" appearance of the epithelium, probably caused by an extreme contraction of the perijunctional actomyosin ring. We conclude that the mucosal explant system is a convenient model for predicting transcellular/paracellular modes of action of novel prospective PEs.